2007
DOI: 10.1007/s11418-007-0138-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Polyalthia parviflora stem

Abstract: From the stem of Polyalthia parviflora, four compounds were isolated, including p-hydroxyphenylethyl p-coumarate (1), p-hydroxyphenylethyl ferulate (2), dehydrodiscretamine (3) and (-)-discretamine (4). Complete 1 H and 13 C NMR assignments were obtained for 1, 3 and 4 for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…8 Traditional healers in Asia use a water decoction of P. parvif lora to treat bodily discomfort. 9 Only one study has investigated the phytochemical constituents of P. parvif lora, reporting the isolation of p-coumarate, p-hydroxyphenylethyl ferulate, dehydrodiscretamine, and (−)-discretamine. 9 Due to the scarcity of reports on P. parvif lora, an extensive phytochemical and biological investigation on the secondary metabolite content of this species was initiated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Traditional healers in Asia use a water decoction of P. parvif lora to treat bodily discomfort. 9 Only one study has investigated the phytochemical constituents of P. parvif lora, reporting the isolation of p-coumarate, p-hydroxyphenylethyl ferulate, dehydrodiscretamine, and (−)-discretamine. 9 Due to the scarcity of reports on P. parvif lora, an extensive phytochemical and biological investigation on the secondary metabolite content of this species was initiated.…”
mentioning
confidence: 99%
“…Hydration and hydrogenation of 7 yield compound 10 and goniothalamin (8), respectively. The oxidation of the double bond between C-7 and C-8 of 8 results in the formation of goniothalamin oxide (9). Epoxide ring opening followed by halogenation (Cl − ) at the appropriate position with the aid of haloperoxidase provides 1.…”
mentioning
confidence: 99%
“…Peaks 22 , 35 , 39 , 50 , 86 , 89 , 94 , and 99 were unambitiously identified by comparison with reference standards. Based on the relevant literature , peaks 11 , 17 , 20 , 30 , 40 , 42 , 43 , 44 , 46 , 51 , 54 , 82 , 139 , and 166 were tentatively assigned. Based on the online database retrieval (Chemspider), peak 26 was tentatively characterized.…”
Section: Resultsmentioning
confidence: 99%
“…Two known cinnamic acid derivatives, p-hydroxyphenethyl-transferulate (4), first extracted from Heracleum lanatum (Nakata et al, 1982) and 2-hydroxyethyl-trans-ferulate (ariscucurbin A) (5), previously isolated from Aristolochia cucurbitifolia (Wu et al, 1999), and 3β,14β-dihydroxy-19-oxo-5β-bufa-20,22-dienolide 3-O-β-D-glucopyranoside (8), reported once previously from the related Madagascan Rhodocodon campanulatus (Schwikkard et al, 2017) were isolated. Compound 4 is a known free-radical scavenger (Hirano et al, 1997) which has also been shown to have an affinity toward serotonin (5-HT 7 ) receptors (Kaewamatawong et al, 2007).…”
Section: Isolation and Characterization Of Compounds From R Rotundus And R Cyathiformismentioning
confidence: 99%